Answer:
C. Na₂SO₄(aq) + Sr(NO₃)₂(aq) → SrSO₄(s) + 2 NaNO₃(aq)
Step-by-step explanation:
Based on the equation:
Na₂SO₄(aq) + Sr(NO₃)₂(aq) → SrSO₄(s) + NaNO₃(aq)
As you can see, sulfate ions (SO₄) are been replaced for nitrate ions (NO₃). That is a double replacement reaction and is a very important information because 2 NO₃ ions in Sr(NO₃)₂ are producing 1 NO₃ ion. To balance NO₃:
Na₂SO₄(aq) + Sr(NO₃)₂(aq) → SrSO₄(s) + 2 NaNO₃(aq)
1 SO₄ ion in Na₂SO₄ produce 1 SO₄ ion in SrSO₄. And Na and Sr metals are balanced yet. Thus, the balanced form of this chemical equation is:
Na₂SO₄(aq) + Sr(NO₃)₂(aq) → SrSO₄(s) + 2 NaNO₃(aq)